2006
DOI: 10.11646/zootaxa.1156.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the pentacrinid stalked crinoids of the genus Endoxocrinus (Echinodermata, Crinoidea), with a study of environmental control of characters and its consequences for taxonomy

Abstract: A revision of the stalked crinoid species attributed to the genus Endoxocrinus A.H. Clark, 1908 (Diplocrininae, Pentacrinitidae, Crinoidea, Echinodermata) is conducted using studies on phenotype variation and its relation with environment. Specimens collected via submersible at five sites in the Bahamas exhibit distinct phenotypes that correlate with different apparent ecological niches and serve as references for interpreting specimens dredged in Atlantic and Pacific Oceans where detailed information on their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…Variations in length of pluri− columnals could influence posture and distribution relative to current flow and topography, as suggested by Messing and Llewellyn (1992). Although David et al (2006) showed clear relationships between environment, morphology, and taxon− omy in the genus Endoxocrinus, these data cannot be directly applied to the Jurassic forms, largely due to the incomplete nature of the dataset in this paper. However, David et al (2007) revealed a link between bathymetry and substrate and the importance of internodals per noditaxis and columnal height to columnal diameter palaeoecoloical reconstruction.…”
Section: Crinoid Autecologymentioning
confidence: 95%
“…Variations in length of pluri− columnals could influence posture and distribution relative to current flow and topography, as suggested by Messing and Llewellyn (1992). Although David et al (2006) showed clear relationships between environment, morphology, and taxon− omy in the genus Endoxocrinus, these data cannot be directly applied to the Jurassic forms, largely due to the incomplete nature of the dataset in this paper. However, David et al (2007) revealed a link between bathymetry and substrate and the importance of internodals per noditaxis and columnal height to columnal diameter palaeoecoloical reconstruction.…”
Section: Crinoid Autecologymentioning
confidence: 95%
“…16353-1 the substrate consisted of carbonate sandstone rock fragments with some coarse carbonate sand (foraminifera ooze) and shell debris and in MSM 20/4 Station 16374-1 of dead coral rubble of about 10 cm length, heavily colonized by diverse epibionts and the stalked crinoid Endoxocrinus (Diplocrinus) maclearanus minimus (Isselicrinidae) (cf. David et al, 2006). diagnosis Body dorsoventrally flattened, short, with up to 50 segments; dorsum more or less covered by elytra or short posterior region uncovered.…”
Section: Distribution and Habitatmentioning
confidence: 99%
“…Taxonomy has been updated following Messing (2001); Messing & White (2001); Roux et al (2002) and David et al (2006). We use the higher classification of Hess and Messing (2011).…”
Section: Methodsmentioning
confidence: 99%
“…Gervais (in Guérin, 1835, Pl. 147, fig.1) translated Parra's description, reproduced his figure, and applied to it the Latin binomen Encrinus parrae (now Endoxocrinus parrae) (A.H. Clark, 1908;David et al 2006). Almost a century after Parra, Pourtalès (1868) described the first comatulid from Cuban waters, Antedon (now Crinometra) brevipinna, collected during the first deep-sea dredging efforts in the western hemisphere (see also Arango & Molina, 1878).…”
Section: Introductionmentioning
confidence: 99%